Productivity, restructuring, and the gains from takeovers - Li, Xiaoyang (Journal of Financial Economics, 2013)
This paper investigates how takeovers create value. Using plant-level data, I show that acquirers increase targets' productivity through more efficient use of capital and labor. Acquirers reduce capital expenditures, wages, and employment in target plants, though output is unchanged. Acquirers improve targets' investment efficiency through reallocating capital to industries with better investment opportunities. Moreover, changes in productivity help explain the merging firms' announcement returns. The combined announcement returns are driven by improvements in target's productivity. Targets with greater productivity improvements receive higher premiums. These results provide some first empirical evidence on the relation between productivity and stock returns in takeovers.